2015
DOI: 10.1007/s13197-015-1753-z
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive and rheological properties of rose hip marmalade

Abstract: In this study, bioactive (total phenolic, antioxidant and antiradical activity) and rheological properties (steady and dynamic) of rose hip marmalade were investigated. Bioactive properties were determined in rose hip marmalade and extract. Extract had higher total phenolic content (38.5 mg GAE/g dry extract), antioxidant activity (124 mg AAE/g dry extract) and antiradical activity (49.98 %) than marmalade. Steady and dynamic rheological properties of the marmalade were determined at different temperature leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 60 publications
1
6
0
1
Order By: Relevance
“…The k value obtained was 47.26, 32.76, and 41.19 Pa·s n for M2, M3, and M4, respectively. A higher value of k was shown as a more consistent jam, 37 and these values were bigger than reported by Sagdic et al 38 for a rosehip jam and within the range shown for peach jam. 39 The n values were less than 1 in all cases, indicating that all samples present shear thinning behavior.…”
Section: Resultssupporting
confidence: 73%
“…The k value obtained was 47.26, 32.76, and 41.19 Pa·s n for M2, M3, and M4, respectively. A higher value of k was shown as a more consistent jam, 37 and these values were bigger than reported by Sagdic et al 38 for a rosehip jam and within the range shown for peach jam. 39 The n values were less than 1 in all cases, indicating that all samples present shear thinning behavior.…”
Section: Resultssupporting
confidence: 73%
“…Parameters 'b' and 'd', for all jam formulations, showed no clear trend considering microalgae addition and sugar or sweeteners addition. Nevertheless, these values were found as positive, further proving the weak gel-like structure of the jams [41].…”
Section: Analysis Of Dynamic Rheological Datamentioning
confidence: 90%
“…изучили биоактивные и реологические свойства мармелада из шиповника, который широко употребляется на завтрак в Турции. Данный мармелад готовят путем варки фруктовой мякоти с сахаром и кислотой до достижения желаемого значения Брикса [12].…”
Section: основная частьunclassified